A Systematic Review of the Efficacy and Safety of Tenecteplase Versus Alteplase in Acute Ischemic Stroke: A Time to Pass the Torch - Miguel Rodriguez; Christian Sidebottom; Drew A. Wells; Thirumalaivasan Dhasakeerthi; Lisa Hayes; Cheran Elangovan; Balaji Krishnaiah (Stroke: Vascular and Interventional Neurology)
Alteplase, a biosynthetic form of human tissue‐type plasminogen activator, is Food and Drug Administration‐approved for the treatment of acute ischemic stroke and currently the standard of care for thrombolytic therapy. Tenecteplase, a modified form of alteplase using recombinant technology, has several pharmacological advantages over alteplase, including longer half‐life, higher fibrin specificity, and greater resistance to plasminogen activator inhibitor‐1. Additionally, tenecteplase is given as a single bolus administration compared to the bolus plus 1‐hour continuous infusion of alteplase. Given these pharmacologic and logistical differences along with studies demonstrating noninferiority compared with alteplase, tenecteplase has become an alternative thrombolytic for the management of acute ischemic stroke. There is a growing body of evidence that suggests tenecteplase is a safe and effective alternative to alteplase. This systematic review evaluates the available literature for the use of tenecteplase in acute ischemic stroke and provides relevant discussion regarding role in therapy, therapeutic strategies, and areas requiring further research.